Analysis of cervicovaginal cytopathologies performed in Bahia between 2015-2019: Technical Indicators (Research, Society and Development, 2021)
Objective: The study aimed to analyze the indicators of cervical-vaginal cytopathologies carried out in Bahia between 2015 and 2019. Methodology: Documentary study, of a quantitative and qualitative nature, of the descriptive type that investigated technical indicators of Pap smear performed by Bahia women aged 25 to 64 years in the period mentioned above, seeking to raise the ratio of examinations performed and the proportion of three-year periodicity and the positivity rates and proportion of unsatisfactory samples. The sample was obtained through secondary data from the Informatics Department of the Unified Health System, specifically using the Cancer Information System, population projections from the Brazilian Institute of Geography and Statistics and the Technical Data Sheet of Indicators of Cancer Control Actions Cervix of the Uterus. The data obtained were registered in the Microsoft Excel 2016 program. Results: The ratio of cytopathological tests was more expressive in 2018 (34.4 tests/100 women/year). The three-year period reached a maximum value (96.6%) in 2017 and a minimum value (94.2%) in 2019. The positivity index peaked in 2019 (2.6%). The proportion of unsatisfactory samples was higher in 2015 (2.4%) with a minimum value in 2017 (1.8%). Final Considerations: The results of this study allow us to infer that there are important gaps to be considered for the full success of the cervical cancer prevention program in the state of Bahia. Thus, it is expected that these results contribute to reflection and taking actions in relation to cervical-vaginal cytopathologies so that we have, in the near future, a minimization in the number of cases of cervical cancer.